2019
DOI: 10.1186/s12889-019-6832-z
|View full text |Cite
|
Sign up to set email alerts
|

Associations between overweight and mental health problems among adolescents, and the mediating role of victimization

Abstract: Background Evidence has not been conclusive on whether adolescent overweight is associated with mental health, possibly caused by indirect, yet untested associations. Therefore, the purpose of this study was to examine the association between overweight or obesity and mental health problems among adolescents, and to determine whether victimization plays a mediating role in these associations. Methods Self-reported data on mental health and victimization and objectively … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
35
0
3

Year Published

2020
2020
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 59 publications
(49 citation statements)
references
References 59 publications
1
35
0
3
Order By: Relevance
“…This suggests that further research focusing on this subject is necessary. As results of previous studies indicate a strong relationship between targeted for being perceived as overweight and mental illness and suicidality among adolescents, it could be assumed that there exists such a relationship between the perception of being underweight and the latter (Haynes, Kersbergen, Sutin, Daly, & Robinson, 2019;van Vuuren et al, 2019).…”
Section: Discussionmentioning
confidence: 99%
“…This suggests that further research focusing on this subject is necessary. As results of previous studies indicate a strong relationship between targeted for being perceived as overweight and mental illness and suicidality among adolescents, it could be assumed that there exists such a relationship between the perception of being underweight and the latter (Haynes, Kersbergen, Sutin, Daly, & Robinson, 2019;van Vuuren et al, 2019).…”
Section: Discussionmentioning
confidence: 99%
“…The difference could be attributed to the variation in socioeconomic condition of the household and energyrelated behavior including behavior of sedentary, physical activities, and eating behavior. Overnutrition in adolescent girls could predispose to different chronic medical illnesses such as cardiovascular, endocrine, gastrointestinal, neurological, psychosocial, and mental health problems [42][43][44]. Therefore, attention shall be given to overweight adolescents through implementing different strategies like creating awareness among the community on healthy feeding practice and physical activities and reducing sedentary life style.…”
mentioning
confidence: 99%
“…Several studies have found that obesity has a negative effect on the physical aspects of health-related QoL and mental health. 38,39,40 None of the participants felt their sexual life was impeded due to their weight before and after the trial. After the trial, the participants' QoL improved, although the items related to public distress remained unchanged.…”
Section: Discussionmentioning
confidence: 99%